2023
DOI: 10.3389/fimmu.2023.1146702
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody responses associate with sex, age and disease severity in previously uninfected people admitted to hospital with COVID-19: An ISARIC4C prospective study

Abstract: The SARS-CoV-2 pandemic enables the analysis of immune responses induced against a novel coronavirus infecting immunologically naïve individuals. This provides an opportunity for analysis of immune responses and associations with age, sex and disease severity. Here we measured an array of solid-phase binding antibody and viral neutralising Ab (nAb) responses in participants (n=337) of the ISARIC4C cohort and characterised their correlation with peak disease severity during acute infection and early convalescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…Clemens A. Schmitt et al 6 reported COVID-19 brought bigger influence in the elderly based on cellular senescence. Furthermore, Parker et al's investigation revealed that individuals aged 41–60 years exhibited higher plasma antibody levels than other age groups 12 . Our finding was consistent with these reported studies.…”
Section: Discussionmentioning
confidence: 99%
“…Clemens A. Schmitt et al 6 reported COVID-19 brought bigger influence in the elderly based on cellular senescence. Furthermore, Parker et al's investigation revealed that individuals aged 41–60 years exhibited higher plasma antibody levels than other age groups 12 . Our finding was consistent with these reported studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that antibody response is delayed in patients with severe COVID-19 [ 33 ]. However, Parker et al found that although antibody levels in patients with severe disease began to rise one to two weeks later than in patients with moderate disease, they later reached similar levels [ 34 ]. Recently, Körper et al reported a trend toward a better outcome in patients receiving CCP from donors with more than three symptoms compared to controls, but the difference was not significant ( p = 0.061) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ancestral SARS-CoV-2 S glycoprotein (Accession MN908947) was cloned into the pCDNA3.1 expression plasmid (produced by GeneArt Gene Synthesis) and was used in generating PVP stocks via a lentiviral system to generate single-cycle infectious viral particles as previously described 52 54 . HEK293T cells (5.0 × 10 5 in each well of a 6-well tissue culture flask) (Corning) were grown in 2.0 mL of complete DMEM overnight.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 S enveloped PVP was used in neutralisation assays as previously described 54 . Serum samples from participants were serially diluted twofold with complete DMEM, and 28 µL serum dilution was incubated with 420 µL diluted SARS-CoV-2 PVP for 30 min at RT.…”
Section: Methodsmentioning
confidence: 99%